Association of rituximab use with adverse events in adults with lymphoma or autoimmune disease: a single center experience - Mengsi Hu; Mengsi Hu; Tingwei Zhang; Tingwei Zhang; Bing Liu; Qi Guo; Bing Zhao; Jiangong Lin; Zhimei Lv; Zhimei Lv; Rong Wang; Rong Wang (Frontiers in Medicine)
ObjectiveRituximab (RTX) is a chimeric human/murine CD20 monoclonal antibody, which has been administered in treating hematological malignancies and various autoimmune disorders. This study aimed to present our center’s experience in RTX use in adults with lymphoma and autoimmune diseases (AID) including primary membranous nephropathy (pMN), as well as therapeutic effects of RTX on clinical outcome of pMN patients.MethodsA total of 761 Chinese patients were retrospectively included, who received RTX treatment at Shandong Provincial Hospital between January 1st, 2017 and December 31st, 2021, with person time of exposure spanning between their first dose of RTX and last follow-up date or the end of the study period.ResultsAdverse events (AEs) occurred in 487 patients (64.0%), with a majority of infection (309, 40.6%) and a minority of non-infectious AEs (178, 23.4%); and the incidences of AEs were higher in lymphoma patients (381, 65.8%) than that in AID patients (106, 58.2%). Respiratory infections (215, 28.3%), gastrointestinal infections (49, 6.4%), urinary tract infections (41, 5.4%), cutaneous and mucosal infections (31, 4.1%), and infections in the abdominal cavity or pleurisy (4, 0.5%) were the leading types of infections. Cancer diagnosis [hazard ratio (HR), 3.926; 95% confidence interval (CI), 1.730–8.913] and prophylactic sulfamethoxazole/trimethoprim (SMZ/TMP) administration (HR, 3.793; 95% CI, 1.101–13.069) were associated with increased risk of infections. Immediate non-infectious AEs included anaphylaxis (44, 5.8%) and infusion reactions (99, 13.0%). Long-term non-infectious AEs included hypogammaglobulinemia (106, 28.6%), neutropenia (11, 5.5%) and interstitial lung disease (1, 0.1%). Female sex (HR, 0.515; 95% CI, 0.289–0.918) and cancer diagnosis (HR, 0.126; 95% CI, 0.049-0.323) were associated with higher risk of hypogammaglobulinemia. In 74 pMN patients, 13 (17.6%) patients experienced infections, with 2 cases of non-infectious AEs (2.7%). 6-month follow-up showed remission was achieved in 45 patients (60.8%), either as initial (61.0%) or alternative therapy (60.7%), without significant impacts on kidney function (p > 0.05).ConclusionOur findings indicated AEs were common during RTX treatment, particularly in lymphoma patients, most of which were moderate and mild, highlighting a whole-process monitoring, timely interference and caring. And RTX was a safe and effective therapeutic option for pMN either as initial or alternative therapy in adult Chinese patients.